Analisa Pengaruh Pemasangan Distributed Generation Pada Jaringan Listrik di Pertamina Ep-Central Processing Plant Area Gundih Menggunakan Software Etap 12.6 - , Yunitasari, Agus Supardi, S.T., M.T (2017)
Distributed Generation (DG) is a small scaled generation of electrical energy which is popular because very effective to improve the voltage and power quality on electrical network. Central Processing Plant (CPP) Area Gundih has a good electrical network system, but the additional load makes the voltage in switchgear worsen. This poor voltage value is represented by the high power losses and voltage drop rating. It certainly will give adverse impact because it can cause the equipment not working properly or not optimal. The purpose of the analysis of distributed generation injection is to discover the effect in voltage value and power quality on power system distribution network in CPP Area Gundih. The method used are as such, gathering data and information directly, followed by making a simulation model of the electrical system and simulate the single line diagram using etap 12.6 software. The results obtained from testing with variation of DG capacity show that the injection of 15 kW DG provide a more effective for lowering the value of power losses and voltage drop than the injection of 35 kW DG, because it can reduce the value of power losses up to 93.68% and lowering the value of a voltage drop to 94.44%. Bus 237 is the most excellent location of the best injection of DG among buses 219, 225, and 227 because it can reduce the power losses to the highest value, it is 93.68% and the voltage drop up to 94.44%.